Quercetin Ameliorates Experimental Autoimmune Myocarditis in Rats - Marina Milenković; Nevena Arsenović-Ranin; Zorica Stojić-Vukanić; Biljana Bufan; Dragana Vučićević; Ivan Jančić (Frontiers Media S.A., 2010)
Purpose: Experimental autoimmune myocarditis (EAM) in rats is an animal model of human giant cell myocarditis and post-myocarditis dilated cardiomyopathy. The pathogenesis of EAM has not been elucidated, but there is accumulating evidence that cytokines secreted from monocytes/macrophages and T cells play a crucial role in the induction and progression of disease. Flavonoids are a large group of polyphenolic compounds abundantly present in the human diet, which scavenge oxygen radicals and have anti-inflammatory activities. Having in mind in vivo beneficial effects of flavonoid quercetin in different animal models of immunoinflammatory diseases such as experimental autoimmune encephalomyelitis and adjuvant arthritis, on the one side, and its in vitro suppressive effect on production of tumor necrosis factor-alpha (TNF-alpha on the other side, we investigated the effects of quercetin on EAM in rats. Methods: Myocarditis was induced in Dark Agouti (DA) rats by injection of porcine cardiac myosin and quercetin at doses of 10 or 20 mg/kg was orally administered from days 0 to 21 after induction of disease. The severity of myocarditis was evaluated by determination of heart weight / body weight ratio (Hw/Bw) and histopathological examination of hearts. The levels of cytokines (TNF-alpha, IL-12, IL-17 and IL-10) in serum and lymph node cells (LNC) culture supernatants were measured by ELISA. Results: The rats treated with 20 mg/kg of quercetin had significantly decreased incidence of EAM, Hw/Bw, macroscopic and microscopic scores of hearts. Further, in EAM rats treated with quercetin levels of TNF-alpha and IL-17 were significantly lower, while the level of IL-10 was significantly higher both in serum and culture supernatants of LNC stimulated with concanavalin A compared with vehicle-treated animals. Conclusions: The present study suggests that quercetin ameliorates EAM, at least in part, by interfering production of proinflammatory (TNF-alpha and IL-17) and/or anti-inflammatory (IL-10) cytokines.